Corn Coffee Maikape - Angelo, Maureen Shine Cebeda, Gwyneth A., Malicsi, Kyla Millen J., Mendoza, John Paul M., Miguel, Kia N., Ortiz, Daniel Bien L., Perez, Althea Bianca B., Ruz, Renee Herminylle C., Umbay, Louisse Dominique Vergel de Dios, Amir Azaraiah S. 4 0 16; 5
u
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2